Family influences on older adults' problem drinking: A representative nationwide study of China - Ye, Yaping; Feng, Jian; Zhang, Yeyuan; Wang, Manli; Chen, Jinsong; Wu, Dan; Kathleen, Young; Jiang, Shuhan (Frontiers in Public Health, 2022)
Abstract Aim: It is reported that problem drinking is severe among the elderly. The family environment has been regarded as a significant effecting factor in alcohol consumption of the drinker. With the increasing number of older people, paying more attention to this vulnerable group’s drinking status and its’ influencing factors is substantial for improving older adults’ health and the quality of health services. Methods: This study used data from the Chinese Longitudinal Healthy and Longevity Study (CLHLS, 2018), which was a representative survey covering 23 provinces in mainland China. Cross-sectional analyses were conducted with 15,142 older individuals (aged ≥65 years). Three self-reported questions about drinking behavior were examined to calculate alcohol consumption and categorize problem drinkers. Three multi-level models were utilized while adjusting for numerous socio-demographic and self-reported health factors to analyze the effect of family factors associated with problem drinking among the elderly. Results: A total of 1800 problem drinkers (12%) were identified in the sample. Key factors for the problem drinker were assessed such as Hukou (governmental household registration system), current marital status, years of schooling, primary caregivers, and financial sources of living were associated with problem drinking. The older population who live in rural areas (OR=1.702,CI=1.453,1.994), with advanced years of education (OR=1.496,CI=1.284,1.744), and making life by themselves (OR=1.330,CI=(1.139,1.552) were more likely to engage in problem drinking while those participants who are widowed (OR=0.678,CI=0.574,0.801), cared for by children or other relatives (OR=0.748,CI=0.642,0.871), adult care giver (OR=0.348,CI=0.209,0.578) or by no one (OR=0.539,CI=0.348,0.835) , provided with financial support from their children (OR=0.698, CI=0.605, 0.806), other relatives (OR=0.442, CI=0.332, 0.587), or the government/community (OR=0.771, CI=0.650, 0.915), with insufficient financial support (OR=0.728, CI=0.608, 0.872) were at lower risk of problem drinking. Conclusions: This study provides a strong correlation of various family factors that were associated with problem drinking among the elderly. The findings underscore the effort to promote healthy behaviors, including the importance of positive family factors and appropriate levels of alcohol consumption.